AN ANALYSIS USING OWAS METHOD FOR IMPROVING EMPLOYEE WORK POSTURE IN OMAH KANDANG SMES - Diansari, Brillian Nur; Saputro, Fery Wisnu; Mu’aafii, Anjab; Cahyo, Anthony Tegar (LPPM Universitas Duta Bangsa Surakarta, 2023)
Omah Kandang SMEs is a SMEs in Surakarta that produce handmade cat cages. The customer of Omah Kandang SMEs scattered in several cities in Indonesia. Unfortunately, the booming demand is still difficult for producer to provide these, it caused by unproductive employee because of poor working postures. This research aims to determine the level of work risk for the employee using OWAS Method and providing suggestions of ergonomics work posture for improving employee productivity. OWAS Method is a method used for body measurement with dividing work activities in several time interval to avoid musculoskeletal disorder risk. The codes in this method includes back, arms, legs and load/use factor. In this research is known that employee work posture in weaving station fall into the category 2. It means unsafe for musculoskeletal system and need an improvement in the future. It is recommended to provide table for ergonomics work posture, so the employee become more productive.